Epidimiology of sheep pox in Greece, during the last thirty years - ΑΞΙΩΤΗΣ Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
The sheep pox appears in Greece during the period 1952-1981 at four different instances i.e. 1956, 1959-1962,1966 and 1972-1973 and takes the form of epizootie. During the second and third instances there were many outbreaks of the disease with important economic losses. Massive vaccination of sheep population took place. The virus does not persist in a latent form in sheep in Greece. Since the 1977, Greece is free of the disease